Endoscopic dacryocystorhinostomy - Rahman, SH; Tarafder, KH; Ahmed, MS; Saha, KL; Tariq, A (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jan;20(1):28-32 The abstract of this article is available on the PubMed website